Monitoring of ecological environment changes in open-pit mines on the Loess Plateau from 1990 to 2023 based on RSEI - Xingbang Wang; Yanyun Nian; Haiyuan Wang; Jie Chen; Kegong Li; Tianming Hu; Zhiming Li (Ecological Indicators)
To address the sustainability challenges of mining, nations and regions have enacted restrictive policies aimed at enhancing ecological environment quality. This study focuses on a typical open-pit lime mine in Yongdeng County, Gansu Province, as a case study to investigate the environmental changes throughout the full life cycle of the mine, from before the start of mining, through peak mining, to the final stage of ecological recovery. Employing the Remote Sensing Ecological Index (RSEI) derived from Landsat satellite imagery spanning 1990 to 2023, we conducted a comprehensive analysis utilizing the Sen + Mann-Kendall method. The results revealed that on the temporal dimension, a non-monotonic trend comprising an initial ascent, a descent, and a subsequent ascent in the ecological environment quality of the study area over the three-decade period. from a spatial perspective, the mining zone regions consistently exhibited a poor ecological state, contrasting with the generally better condition observed in non-mining regions. These results can provide reference for the ecological environment governance of open-pit mines.